2021
DOI: 10.1002/hep4.1698
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental DUAL Model of Advanced Liver Damage

Abstract: Individuals exhibiting an intermediate alcohol drinking pattern in conjunction with signs of metabolic risk present clinical features of both alcohol-associated and metabolic-associated fatty liver diseases. However, such combination remains an unexplored area of great interest, given the increasing number of patients affected. In the present study, we aimed to develop a preclinical DUAL (alcohol-associated liver disease plus metabolic-associated fatty liver disease) model in mice. C57BL/6 mice received 10% vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Dysregulation of MCJ was further confirmed using the DUAL dietary model by WB and gene expression (Figure 1C, Supplemental Figure 1b, http:// links.lww.com/HEP/C648). [16] In light of these results, we aimed to understand the mechanism by which the expression of Mcj is regulated after alcohol consumption. Mcj has been previously reported to be epigenetically regulated in NAFLD.…”
Section: Mcj Expression In Human Liver With Severe Ahmentioning
confidence: 99%
“…Dysregulation of MCJ was further confirmed using the DUAL dietary model by WB and gene expression (Figure 1C, Supplemental Figure 1b, http:// links.lww.com/HEP/C648). [16] In light of these results, we aimed to understand the mechanism by which the expression of Mcj is regulated after alcohol consumption. Mcj has been previously reported to be epigenetically regulated in NAFLD.…”
Section: Mcj Expression In Human Liver With Severe Ahmentioning
confidence: 99%
“…In an experimental approach, Benedé-Ubieto et al have developed a preclinical DUAL model in mice (alcohol-associated liver disease plus MAFLD), which mimics all histological, metabolic, and transcriptomic gene signatures of human advanced steatohepatitis. Hence, it could serve as a preclinical tool for the development of therapeutic approaches [42].…”
Section: Discussionmentioning
confidence: 99%
“…While the WDA model differs considerably from Lieber-DeCarli and Tsukamoto-French models of ALD, several prior studies have also examined the effects of alcohol in drinking water, combined with various diets on liver pathology. Several of these studies added alcohol to diets already known to produce a NASH-like liver injury and showed enhancement of both inflammation and fibrosis by the added alcohol (Benedé-Ubieto et al, 2021;Sengupta et al, 2021).…”
Section: Discussionmentioning
confidence: 99%